Three-dimensional numerical study of a local scour downstream of a submerged sluice gate using two hydro-morphodynamic models, SedFoam and FLOW-3D - Ghzayel, Alaa; Beaudoin, Anthony (Comptes Rendus. Mécanique)
Three-dimensional numerical simulations were performed, based on an experimental study of sediments scour process subjected to a water jet downstream of a submerged sluice gate with a rectangular opening at the bottom in a very confined channel. This experimental geometry, little studied in the literature, presents two particular phenomena in the dynamics of the scour process: a change of the dune form and a digging - refilling cycles of the scour. Two different hydro-morphodynamic models, SedFoam and FLOW-3D, were used and calibrated according to the experimental data. SedFoam is a multiphase flow model based on the open-source tool-box OpenFOAM and uses a coupling method between the fluid and particles phases in the RANS equations through the dense granular rheology, while FLOW-3D is an CFD software that uses a sediment scour model to perform sediment transport through bedload and suspended load transport equations without direct coupling with the fluid phase. The use of these specific three-dimensional numerical models in the case of the water flow with a jet in a very confined channel has allowed to evaluate the accuracy of turbulence models used. The RNG $K-ε $ turbulence model was used in FLOW-3D while the $K-ω $ turbulence model was used in SedFoam. The RNG $K-ε $ turbulence model is more numerically stable for a finer mesh size. Based on the comparison of the three-dimensional numerical results with the experimental data, a discussion has allowed to explain the two particular phenomena in the dynamics of the scour process, a change of the dune form and a digging - refilling cycles of the scour, observed in the experimental data. It was concluded that the dune shape-shifting is due to the hydro-morphodynamic behaviour of the interaction of fluid-particles in presence of high degree of confinement while the digging - refilling phenomenon is explained by the physical mechanics behaviour of the particles phase due to gravity.